MIGRATION, MEMORIES & MISERY IN THE GLASS PALACE BY AMITAV GHOSH - Iqbal, Fayezah; Khushboo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The history of Indo-Myanmar migration from the late 19th to 20th century has been a subject of great curiosity among many researchers and authors and is quite well-documented and much written about. The Glass Palace by Amitav Ghosh is one of them that narrates the stories of Rajkumar and Dolly in the backdrop of the Third Anglo-Burmese War of 1885, the rapid influx of indentured laborers to Burma since the early 20th century and the mass emigration of Indians in 1942 from Burma in the wake of the Second World War. On the other hand, the research paper, Indian-Migrants in Myanmar: Emerging Trends and Challenges published under the Ministry of Overseas Indian Affairs gives a thorough and succinct explanation of facts about the different phases of migration from India to Burma and its social and political repercussions. This research paper attempts to concurrently study the portrayal of these events as essayed in novel to the observation of facts in the paper.